KEPEMIMPINAN WAKIL KEPALA SEKOLAH BIDANG KURIKULUM DALAM MENERAPKAN KEBIJAKAN MERDEKA BELAJAR DI SMK NEGERI 2 DEPOK KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - Rizki Kurniati; Khairul Rofiah; Sabarudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This article analyses the responsibilities of the Deputy Principal for Curriculum in executing the Independent Learning Policy at SMK Negeri 2 Depok in Sleman Regency, Special Region of Yogyakarta. The study was conducted at SMK Negeri 2 Depok, situated in Sleman Regency, within the Special Region of Yogyakarta. This study is a qualitative research that employs a case study methodology to investigate the leadership of the Deputy Principal for Curriculum in implementing the Independent Learning Policy at SMK Negeri 2 Depok Sleman in Sleman Regency, Special Region of Yogyakarta. The main objective is to characterise the leadership practices in this context. The investigation focused on a single individual, specifically the deputy principal responsible for curriculum. The research utilised a range of data collection methods, including interviews, observations, and document analysis. Data analysis involves various techniques, including data reduction, data visualisation, and drawing conclusions. The results suggest that the deputy principal in charge of the curriculum at SMK Negeri 2 Depok in Sleman Regency, Special Region of Yogyakarta, has a clear understanding of the concept of independent learning policy and actively contributes to the development of activity programmes at the school. Effective implementation of autonomous learning necessitates seamless communication among the deputy principal for curriculum, the principal, and teachers, along with robust support for collaboration and teacher involvement in industry-focused skills enhancement.